A Turkish Drama in the Land of Telenovelas. The Reception of ‘Fatmagul’ in Brazil - Gabrielle Ferreira (Series. International journal of tv serial narratives, 2023)
Brazil is well-known for its consolidated television industry that produces and exports telenovelas since the 1970s. However, a new phenomenon took place in the country in 2015: free-to-air television network Band started to air Turkish TV dramas. Fatmagul, the second Turkish drama broadcast by Band, achieved considerably high audience ratings and engaged audiences online. In this work, I rely on discussions about melodrama and transnational media flows to investigate Brazilian viewers' perceptions of Fatmagul. More specifically, my research questions are 1. how is this foreign narrative related to the context of Brazilian audiences' daily lives? and 2. what differences and similarities do Brazilian audiences see between Turkish and Brazilian productions regarding the narrative content? To gather data on the audience profile and general preferences, I shared an online questionnaire on groups about Fatmagul on Facebook. Among the respondents, I selected five female viewers from varied backgrounds and conducted in-depth interviews. The results point out that viewers relate to the melodramatic structure and moral of Fatmagul, especially concerning the emphasis on romance and the protagonist overcoming obstacles. Results also suggest that viewers reject more realistic narratives presented by Brazilian telenovelas, which they consider too sexualized and not family-oriented.